Analysis Of Differences In The Adequacy Of Breast Milk Production In Hormonal Family Planning Acceptors - Lestari, Aldina; Nabila (Jurnal Life Birth, 2017)
According to Basic Health Research data (2013), the use of family planning for the national figure has increased from 55.8% (2010) to 59.7% (2013). Hormonal contraception users (84.57%) and non hormonal (19.35%). Where the coverage of exclusive breastfeeding in Indonesia in 2015 is only (55.7%). The factors that affect milk production are the use of contraceptives.The purpose of this study is to know the difference in the adequacy of breast milk production in hormonal family planning acceptors in the working area of ​​Caile Health Center, Ujung Bulu District, Bulukumba Regency.This study uses an observational analytic design with a "cross-sectional" approach. The population in this study were 52 people and a sample of 39 respondents who were determined using consecutive sampling techniques. Data collection was carried out using observation sheets and questionnaires. The results of the analysis using the Fisher Exact statistical test or an alternative to the Chi-Square test through the cell merging process showed that the value of p = 0.028 or smaller than the value of α = 0.05, which means there is a difference in the adequacy of breast milk production in hormonal KB acceptor mothers.The conclusion in this study is that there are differences in the adequacy of breast milk production in hormonal family planning acceptors in the work area of ​​Caile Health Center, Ujung Bulu District, Bulukumba Regency. Researchers suggest that mothers who are breastfeeding can choose and use an appropriate contraceptive while breastfeeding so that it does not interfere with the lactation process.